Mechanistic Dichotomy in the Asymmetric Allylation of Aldehydes with Allyltrichlorosilanes Catalyzed by Chiral Pyridine N‐Oxides. Issue 28 (6th June 2013) - Malkov, Andrei V.; Stončius, Sigitas; Bell, Mark; Castelluzzo, Fabiomassimo; Ramírez‐López, Pedro; Biedermannová, Lada; Langer, Vratislav; Rulíšek, Lubomír; Kočovský, Pavel
Abstract: Detailed kinetic and computational investigation of the enantio‐ and diastereoselective allylation of aldehydes1 with allyltrichlorosilanes5, employing the pyridine N ‐oxides METHOX (9 ) and QUINOX (10 ) as chiral organocatalysts, indicate that the reaction can proceed through a dissociative (cationic) or associative (neutral) mechanism: METHOX apparently favors a pentacoordinate cationic transition state, while the less sterically demanding QUINOX is likely to operate via a hexacoordinate neutral complex. In both pathways, only one molecule of the catalyst is involved in the rate‐ and selectivity‐determining step, which is supported by both experimental and computational data. Abstract : Kinetic and computational investigations of the enantio‐ and diastereoselective allylation of aldehydes with allyltrichlorosilanes, employing METHOX as chiral organocatalyst, indicate that the reaction proceeds through a dissociative (cationic) mechanism with a pentacoordinate cationic transition state (see scheme). The less sterically demanding QUINOX catalyst operates via a hexacoordinate neutral complex. In both pathways, only one molecule of the catalyst is involved in the rate‐ and selectivity‐determining step.